2017
DOI: 10.1257/pol.20130426
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Consumption Behavior: Evidence from Consumers' Reaction to Shopping Vouchers

Abstract: This paper advances our understanding of consumption behavior using the 2009 Taiwan Shopping Voucher Program. This program was universal and well publicized, and its payment to each individual was medium-sized. Based on survey data, it is found that the marginal propensity to consume is about one quarter, which is comparable to findings obtained by previous studies on consumers' response to fiscal stimulus payments. Further, vendors' discounts for voucher users played a significant role in boosting the effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 9 publications
1
29
0
Order By: Relevance
“…A large literature explores the marginal propensity to consume from unanticipated income shocks. For example, Kan, Peng, and Wang (2017) analyze a $2.6 billion shopping voucher program in Taiwan and find that each dollar of vouchers leads to $0.24 of increased spending. Fagereng, Holm, and Natvik (2019) use lottery winners in Norway to measure the MPC for lottery prizes, which range from around 50% for highliquidity winners of large prizes to 100% for low-liquidity lottery winners who win small prizes.…”
Section: Introductionmentioning
confidence: 99%
“…A large literature explores the marginal propensity to consume from unanticipated income shocks. For example, Kan, Peng, and Wang (2017) analyze a $2.6 billion shopping voucher program in Taiwan and find that each dollar of vouchers leads to $0.24 of increased spending. Fagereng, Holm, and Natvik (2019) use lottery winners in Norway to measure the MPC for lottery prizes, which range from around 50% for highliquidity winners of large prizes to 100% for low-liquidity lottery winners who win small prizes.…”
Section: Introductionmentioning
confidence: 99%
“…The coupons will be accepted at an estimated 140,000 restaurants around Taiwan, as well as 280,000 businesses in shopping centers, 10,000 night markets, and 1,700 arts and culture spots.17 There is a NT$ 2.2 billion administrative cost for the coupons. Based on the MPC estimates fromKan et al (2017) Dr. Kan estimated in a conference in August that it can only contribute to a 0.08 percent GDP (around NT$ 15.27 billion) increase.…”
mentioning
confidence: 99%
“…Publicity can be achieved through government marketing campaigns, but also through accompanying promotional activities by companies. For example, Kan, Peng, and Wang (2017) found that vendors' discounts for a voucher program significantly increased the effectiveness of this policy tool.…”
Section: Effectiveness Of Tax Policy Measures To Stimulate Consumptionmentioning
confidence: 99%